Puff or pass: do social media and social interactions influence smoking behaviour of university students? A cross-sectional mixed methods study from Dhaka, Bangladesh. Issue 11 (3rd November 2020) - Roby, Naym Uddin; Hasan, M Tasdik; Hossain, Sahadat; Christopher, Enryka; Ahmed, Md Kapil; Chowdhury, Ariful Bari; Hasan, Shahriar; Ashraf, Fatema
Abstract : Objective: To determine whether the odds of being a smoker differ based on social media use and social interactions among urban university students in Bangladesh. Hypothesis: Social media use and social interactions influence the smoking behaviour of Bangladeshi university students, particularly in starting and maintaining cigarette smoking. Design and setting: A cross-sectional study using mixed methods on 600 student smokers and non-smokers recruited from two public and two private universities in Dhaka, Bangladesh, a lower middle-income country with limited resources. Exclusion criteria were those who did not use any form of social media and PhD students. Results: Odds of smoking were significantly higher for those who socialised more than 4 hours/day (p<0.05; OR 1.75; 95% CI 1.12 to 2.75) and typically at night (p<0.05; OR 2.80; 95% CI 1.95 to 4.00). Odds of smoking were also higher for those who liked (p<0.05; OR 4.85; 95% CI 3.32 to 7.11), shared (p<0.05; OR 20.50; 95% CI 13.02 to 32.26) and followed (p<0.05; OR 2.88; 95% CI 1.36 to 6.11) tobacco-related content on social media. Qualitative analysis resulted in emergent themes of smokers imitating tobacco-related photos or videos seen on social media and peers as an influence for smoking initiation. Conclusion: This study suggests social media and social interactions may influence smoking behaviour in university students in Dhaka, Bangladesh. Future research should continue to investigate the roles social media and social interaction have on smoking in order to explore social media-based smoking cessation interventions or dissemination of smoking health hazards through social media.